2021
DOI: 10.3390/healthcare9111534
|View full text |Cite
|
Sign up to set email alerts
|

Functional Settings of Hospital Outdoor Spaces and the Perceptions from Public and Hospital Occupant during COVID-19

Abstract: Hospital outdoor spaces play an important role for the safety and well-being of users (patients, visitors, and staff), particularly during a pandemic. However, the actual needs of these spaces are often overlooked due to the design and management process. This study investigates the perceptions of the public and occupants on the functional settings of outdoor spaces, and provides evidence for building a safe and resilient hospital during (and after) COVID-19. A multi-method approach of web content analysis (WC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Decontamination outdoor areas should be provided close to the ED, possibly facing the entrance, where temporary and semi-temporary prefabricated volumes (or canopies) can be placed to ensure a confined space with a buffer and pre-triage function. 12 In conclusion, the atrium and waiting areas should be enough dimensioned to facilitate spacing and convertibility to emergency care spaces (easily implemented oxygen and vacuum dispensing facilities should be provided for this purpose).…”
mentioning
confidence: 99%
“…Decontamination outdoor areas should be provided close to the ED, possibly facing the entrance, where temporary and semi-temporary prefabricated volumes (or canopies) can be placed to ensure a confined space with a buffer and pre-triage function. 12 In conclusion, the atrium and waiting areas should be enough dimensioned to facilitate spacing and convertibility to emergency care spaces (easily implemented oxygen and vacuum dispensing facilities should be provided for this purpose).…”
mentioning
confidence: 99%
“…While some researchers have concentrated on designing the space planning [50] and layout of hospitals, Ma et al examined the public and occupant perceptions of the functional settings of outdoor spaces. Their results revealed that a lack of alignment between the outdoor space and users' emerging functional needs led to low satisfaction and high expectations [51]. A study conducted at inpatient units of a public hospital in Malaysia indicated that the respondents were dissatisfied with the space planning and furniture [52].…”
Section: Occupant Satisfaction In Hospitalmentioning
confidence: 99%
“…Second, hospital outdoor spaces should be accessible, welcoming, and satisfy the needs and requirements of all users, including the ability to relax, view, stroll, exercise, and interact with each other (Iqbal, 2021b; Bengtsson & Grahn, 2014). Lastly, in planning for hospital outdoor spaces, adequate considerations should be given to choosing the right location: away from traffic and other pollution sources, while ensuring that the spaces are neat, safe, have a well-kept landscape and vegetation type that does not deteriorate air quality through pollen, and devoid of hardscape designs (e.g., concrete), overcrowding, loud noise, and smoking (Ma et al, 2021; Ulrich, 2002). Lack of space and resources should not hinder the creation of outdoor gardens as their potential benefits outweigh the economic concerns.…”
Section: The Way Forwardmentioning
confidence: 99%
“…The literature advocate and reiterate the importance of having outdoor spaces and facilities (Nedučin et al, 2010; Sadatsafavi et al, 2015; Shukor, 2012), gardens/healing gardens (Hartig & Marcus, 2006; Marcus, 2016; Ulrich, 2002), contact with nature (Elantary et al, 2021; Trau et al, 2016), and therapeutic environments (Thaneshwari et al, 2018) in healthcare settings and their health and psychological benefits to different users including patients, staff, and visitors. However, the pandemic has especially underscored the importance of hospital outdoor landscaped spaces and access to nature for healthcare staff who spend a considerable part of their lives in healthcare environments with an increased risk of contracting COVID-19 virus from infected patients (Gregory et al, 2022; Ma et al, 2021; Vizheh et al, 2020). Certainly, given the higher exposure to health and safety-related risks during the pandemic, caring for the well-being of healthcare workers is an important issue worthy of consideration by healthcare sector stakeholders (Sethi et al, 2020; Xu et al, 2021).…”
Section: Importance Of Hospital Outdoor Spaces During the Covid-19 Pa...mentioning
confidence: 99%